Survey Data for Mapping Technology Adoption in East and Central Africa - International Food Policy Research Institute; Association for Strengthening Agricultural Research in Eastern and Central Africa (International Food Policy Research Institute, 2017)
This dataset include survey instrument and data used in a collaborative technology adoption study conducted by the Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) and IFPRI. The study aimed to track the adoption and diffusion of selected technologies generated and promoted by in Tanzania, DRC and Rwanda. The studies were undertaken under the "Monitoring the Geospatial Diffusion of Agricultural Technologies" project funded Research Program on Policies, Institutions and Markets (PIM). The studies involved use of cost-effective ICT-based survey technique to track adoption and diffusion of agricultural technologies and explore scalable options for monitoring farmer's use of agricultural technologies. This innovative approach sought to document extent of technology adoption and diffusion over time and space since there is little evidence in this area with other approaches. The main objective of the survey was to test innovative methodologies for tracking adoption and generate data, knowledge and information on how far the agricultural technologies have been adopted by smallholder farmers and diffused over time and space. The specific objectives of the diffusion surveys were to: (i) establish the level of adoption of the technologies promoted by ASARECA within the target countries; (ii) identify, track and map out new areas where the technologies promoted by ASARECA have been adopted and diffused over time within the target countries; (iii) identify factors that are limiting the adoption of the technologies promoted by ASARECA within the target countries; and (iv) establish why farmers have stopped using the technologies and estimate level of technology dis-adoption among the target farmers. These studies looked at two technologies promoted by ASARECA within the region: QPM in Tanzania and DRC; and Climbing beans in Rwanda. Survey tools developed by IFPRI in collaboration with ASARECA and implemented as the TechTracker Survey Application developed by Spatial Development International.